En rullande cykel : Cykelreparation för den oinsatte - Mattsson, Ludvig (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
It is no secret that the world is facing major climate challenges. One of the aspects that can contribute to a greener future is to reconsider our means of transport. That bicycles is part of the solution and also contributes to the public health is something that is gaining more and more traction in society. An aspect though, that has received far too little attention and is the basis of this work is broken-down, stationary bicycles. Something that neither benefits the individual nor society at large. What this work aims to explore is why this happens, how it can be avoided and how to get bike owners to actually repair their bikes. This through a user-centered design process that is based on the users' situation and needs. This project is a bachelor’s thesis within industrial design engineering that has been carried out during spring 2022 at Luleå University of Technology. Through a user-centered process based on several methods such as guerilla interviews, participatory observation, and context research, a broad picture of the current situation was created. Based on this, creative methods such as brainstorming and workshops were then used to create a large number of ideas based on the users' needs. A thorough idea evaluation, mockups and a dot-voting then sifted these ideas down to a final concept where wireframes and prototyping ensured that the concept could be realized. The result of the project was the following; users don’t repair their bikes because they are insecure, lack knowledge and do not trust their abilities. They consider repairing to be a project that feels tedious and difficult to begin with. The users need a simple, clear solution that creates security and presents relevant information. The solution landed in the concept A rolling bicycle consisting of two parts and a total of three steps. The first part is a number of posters to create incentives to repair one's bike and the second part an application that contains both a guide before the repair, but also instructions during the repair ...